River Cruise Tourism Development with Focus on Fish Nurseries and Land Revitalization in Rempanga Village - Surya Ningsih, Novita; Zuraidah, Syarifah; Putri, Naiya Azzahra; Ardelia, Diva Laili; Farah, Aqila Zahwa Nur; Inayah, Husnul; Ananta, Dyah Fitri; Carla, Esya; Mongan, Revier Edgardo; Patria, Helmi; Rahman, Taufikur; Chaniago, Muhammad Fariz Apriza (Golden Ratio of Community Services and Dedication, 2025)
Rempanga Village in Kutai Kartanegara Regency is one of many areas in East Kalimantan actively focusing on sustainable tourism development. This article discusses how river cruises can promote tourism while also promoting conservation. To protect the ecosystem, this practice is followed by fish nurseries and land revitalization. The purpose of this study is to see how river cruises can promote environmental conservation and improve the welfare of local communities. The approach used in this research study was descriptive qualitative and data were collected through documentation studies, interviews, and observations. The results showed that although river cruises have a lot of potential to grow, there are a number of obstacles that stand in the way. Combining tourism and conservation efforts can be a powerful way to address these issues. Fish nurseries and land restoration can not only help with environmental conservation, but also make a destination more attractive to tourists. According to the study findings, Rempanga Village's decision to introduce river cruises is a reasonable first step towards achieving sustainable tourism.